ANALISIS YURIDIS TINDAK PIDANA KECELAKAAN LALU LINTAS BERAKIBAT KEMATIAN (STUDI PENELITIAN DIWILAYAH HUKUM POLRES KOTA LHOKSEUMAWE) - Wahyu Maulana (Fakultas Hukum Universitas Malikussaleh, 2018)
The Law Number 22 of 2009 on Traffic and Transportation has given juridical regulation to traffic order. Numerous traffic accidents in the area of police station of Lhokseumawe city from 2016 to 2018 occurred due to the negligence of driver that cause casualties even death. The study aimed to describe the criminal act of traffic accident fatality and the causes in the area of Police Station of Lhokseumawe. The study also attempted to examine the efforts of the traffic police of police station in Lhokseumawe to manage the criminal act of traffic accident fatality and the obstacles. This study used qualitative methods with sociological juridical approach. Data obtained through library research and field research. Data analysis was conducted by using descriptive analysis. Based on the results, it can be concluded that the criminal act of traffic accident fatality in the area of police station in Lhokseumawe is caused by negligence (culpa) of driver and noncompliance with the traffic laws. Majority of the accident is caused by one vehicle overtaking another vehicle. While the efforts to manage violations of traffic law was carried out preventively and repressively by the police station of Lhokseumawe. However, it might not be able to eliminate the violation directly but it can give a warning to the traffic violator. To present an intact image of law to the public, it is suggested that the traffic police of Lhokseumawe city to handle traffic accidents using the strategy of single site (fixing sharp bend), mass action plans (coating the road surface), route action plans (improving traffic signs facilities), and area wide schemes (reducing vehicle speed on specific location), as well as improvements in the internal of police station in Lhokseumawe city. Keywords: Juridical Analysis, Criminal Act, Accident, Traffic